Risk-Adjusted Returns of American Depositary Receipts on Chinese and Indian Stocks - Arugaslan, Onur (Universiti Utara Malaysia, 2009)
This study evaluates the risk-adjusted performance of American Depositary Receipts (ADRs) on shares of stock of Chinese and Indian fi rms.The first part of the study examines the nature of Chinese and Indian ADRs (based on depositary bank, sponsorship status, industry classification and listing).The second part of the study evaluates the performance of these ADRs using statistical measures grounded in modern portfolio theory. Returns are adjusted for the degree of total risk and systematic risk inherent in each ADR, and the securities are then ranked on the basis of risk-adjusted performance.Two relatively new evaluation metrics, the Modigliani and Sortino measures, are used. The objective of the study is to provide documentation to global investors who are contemplating participation in Chinese and Indian stock markets via depositary receipts.